2021
DOI: 10.1177/20592043211014014
|View full text |Cite
|
Sign up to set email alerts
|

Musical Preference: Role of Personality and Music-Related Acoustic Features

Abstract: Personality factors, typically determined by the Big Five Inventory (BFI), have been a primary method for investigating individual preferences in music. While these studies have yielded a number of insights into musical choices, weaknesses exist, owing to the methods by which music is characterized and categorized. For example, musical genre, music-preference dimensions (e.g., reflective and complex), and musical attributes (e.g., strong and mellow), reported within the literature, have arguably produced incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, a meta-analysis on the correlation between musical style preferences and personality concluded that the effect sizes for Openness were only small, and the remaining Big Five dimensions exhibited inconsistent or no associations in this line of music research (Schäfer & Mehlhorn, 2017). These findings may relate, at least in part, to the high degree of abstraction in past studies measuring music preferences via broad genre and style categorizations, which lack a distinct definition by musical properties and, thus, prevent conclusions about the aspects of music relating to personality dimensions (Aucouturier & Pachet, 2003;Flannery & Woolhouse, 2021;Rentfrow et al, 2011). Specifically, genre preferences contain inconsistent meta-information about the preferred music, like the music's geographical origin (e.g., Latin), its popularity (e.g., Pop), or stereotypes associated with the music's fans (e.g., Punk; Rentfrow & Gosling, 2007).…”
Section: Musical Style Preferencesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a meta-analysis on the correlation between musical style preferences and personality concluded that the effect sizes for Openness were only small, and the remaining Big Five dimensions exhibited inconsistent or no associations in this line of music research (Schäfer & Mehlhorn, 2017). These findings may relate, at least in part, to the high degree of abstraction in past studies measuring music preferences via broad genre and style categorizations, which lack a distinct definition by musical properties and, thus, prevent conclusions about the aspects of music relating to personality dimensions (Aucouturier & Pachet, 2003;Flannery & Woolhouse, 2021;Rentfrow et al, 2011). Specifically, genre preferences contain inconsistent meta-information about the preferred music, like the music's geographical origin (e.g., Latin), its popularity (e.g., Pop), or stereotypes associated with the music's fans (e.g., Punk; Rentfrow & Gosling, 2007).…”
Section: Musical Style Preferencesmentioning
confidence: 99%
“…Only a few pioneer studies have assessed preferences for individual audio characteristics and revealed differential associations with the Big Five personality traits. Thereby, Openness was correlated to preferences for slow tempo, minor mode, acoustic sounds, and negative valence, while Extraversion was related to preferences for major mode, high tones, and positive valence (Dobrota & Reić Ercegovac, 2017;Flannery & Woolhouse, 2021;Fricke & Herzberg, 2017;Vuoskoski & Eerola, 2011).…”
Section: Musical Attribute Preferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic two-way interaction between music training and personality has become the focus of psychological research in recent years. On the one hand, personality characteristics can affect individuals’ music preferences ( Flannery and Woolhouse, 2021 ), music-induced movement or dancing style ( Luck et al, 2010 ), and the durability and effectiveness of music training ( Swaminathan and Schellenberg, 2018 ) across different ages ( Luo et al, 2014 ). On the other hand, music training can improve the personality characteristics of individuals.…”
Section: Introductionmentioning
confidence: 99%